Rozwiąż równania:
a)4x-3 = 3x+5
b)5x+2 = 7-3x
c)3(x-1) = 0
d)-6(x-2) = 3x-1
e)-7(x-2) = 3x-1
f)4(x-1) = 6(1+x)
g)0,2x+0,3 = -0,5
h)0,4+0,25x = -2
i)2,1-0,3x = 0,4x
j)-1,5x-3 = 0,2x+6
k)1/2x-4 = x-6
l)x-5 = 1/3x+1
m)x/4-1/4 = 2
n)x/5-3+x+1/5
o)5/6(x-1) = 4
p)-1/2 (-x-6) = -x


=)

2

Odpowiedzi

2010-04-07T15:39:13+02:00
A)4x-3 = 3x+5
x=8

b)5x+2 = 7-3x
8x=5 /8
x= 5/8

c)3(x-1) = 0
3x-3=0
3x=3 /3
x=1

d)-6(x-2) = 3x-1
-6x+12=3x-1
-9x=-13 / (-9)
x= 1 4/9

e)-7(x-2) = 3x-1
-7x+14=3x-1
-10x=-15 /(-10)
x= 1 1/2

f)4(x-1) = 6(1+x)
4x-1=6+6x
-2x=7 /(-2)
x=-3 1/2

g)0,2x+0,3 = -0,5
0,2x=-0,5-0,3
0,2x=-0,8 /(0,2)
x= -4

h)0,4+0,25x = -2
0,25x=-2-0,4
0,25x=-2,4 /0,25
x= -9,6

i)2,1-0,3x = 0,4x
-0,7x=-2,1 /(-0,7)
x= 3

j)-1,5x-3 = 0,2x+6
-1,7x=9 /(-1,7)
x=-5,30

k)1/2x-4 = x-6
1/2x-x=-6+4
-1/2x=-2 / (-1/2)
x=4

l)x-5 = 1/3x+1
x-1/3x=1+5
2/3x=6 /(2/3)
x= 9

m)x/4-1/4 = 2 /*4
x-1=8
x=9

n)x/5-3+x+1/5 / *5
x-15+5x+1=0
6x=14 /6
x=2 1/3

o)5/6(x-1) = 4 /*6
5x-5=24
5x=29 /5
x=5 4/5

p)-1/2 (-x-6) = -x /*2
x+6=-2x
3x=-6 /3
x=-2
Najlepsza Odpowiedź!
2010-04-07T15:39:47+02:00
A)4x-3 = 3x+5
x= 8

b)5x+2 = 7-3x
8x= 5 /:8
x= 0,625

c)3(x-1) = 0
3x-3=0
3x=3 / :3
x=1

d)-6(x-2) = 3x-1
-6x+12=3x-1
-9x=-13 /: (-9)
x= 1,(4)

e)-7(x-2) = 3x-1
-7x+14=3x-1
-10x=-15 /: (-10)
x= 1,5

f)4(x-1) = 6(1+x)
4x-4=6+6x
-2x=10 /: (-2)
x= -5

g)0,2x+0,3 = -0,5
0,2x=-0,8 /: O,2
x= -4

h)0,4+0,25x = -2
0,25x=-2,4 /: 0,25
x=-9,6

i)2,1-0,3x = 0,4x
-0,7x=-2,1 /: (-0,7)
x=3

j)-1,5x-3 = 0,2x+6
-1,7x=9 /: (-1,7)
x≈ 5,3

k)1/2x-4 = x-6
-0,5x=2 / : (-0,5)
x= -4

l)x-5 = 1/3x+1
2/3x=6 /: 2/3
x=9

m)x/4-1/4 = 2 / *4
x-1=8
x=7

o)5/6(x-1) = 4
5/6x-5/6=4
5/6x=3, 1/6
x= 3,8

p)-1/2 (-x-6) = -x
1/2x+3=-x
1,5x=-3 /: 1,5
x=-2